Efektivitas Penggunaan Biji Kelor (Moringa OleÃfera, Lam) Sebagai Koagulan Untuk Menurunkan Kadar TDS dan TSS Dalam Limbah Laundry - Hak, Ahsanul; Kurniasih, Yeti; Hatimah, Husnul (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Laundry waste contains detergent which can cause water pollution because it contains various kinds of substances that can affect various water parameters, especially such as TDS (total dissolved solids) and TSS (total suspended solids). To reduce these parameters is done by the coagulation process which is adding moringa seed powder as coagulant. Moringa seeds can work as a coagulant because they contain an active substance, 4-alfa-4- rhamnosyloxy-benzil-isothiocyanate. The coagulation process was carried out by varying several coagulation parameters such as the size of the coagulant powder (Al (80-100mesh) and A2 (100mesh), stirring speed (slow, medium, and fast), settling time (15, 45 and 75 minutes) and mass ratio to sample volume (100 mg against 100, 150 and 200 mL) .The samples used in the coagulation process were taken by grab sampling technique and the determination of TDS and TSS levels was carried out by the gravimetric method. The data showed the size of moringa seed powder coagulant, stirring speed, settling time and coagulant mass ratio with sample volume influence the% decrease in TDS and TSS levels, optimum conditions on coagulant powder size> 100 mesh, moderate stirring speed, 15 minute deposition time and coagulant mass ratio to sample volume 1: 1 ( mg / L), where% decrease in TDS is 74.07% from 270000 mg / L to 70000 mg / L and TSS of 82.14% from 56000 mg / L to 10000 mg / L.